Oxford History for Pakistan - Moss, Peter 1921- (Karachi Oxford University Press, 1998)
This regional study, focusing on the South Asian subcontinent, brings together a range of information on natural conditions, irrigation works, environmental effects of landholding structures, and crop patterns in the first half of the 20th century.
Include Index and Color Illustrations
"A revised and expanded version of The Oxford history project.
Keywords: World history -- Pakistan -- South Asia